If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-83=10x-22
We move all terms to the left:
3x-83-(10x-22)=0
We get rid of parentheses
3x-10x+22-83=0
We add all the numbers together, and all the variables
-7x-61=0
We move all terms containing x to the left, all other terms to the right
-7x=61
x=61/-7
x=-8+5/7
| 22=x/3+9 | | 38-2c+c=2(c+5)+c | | 0.1=x-(0.7x+0.25) | | 6n+5n=495 | | 2/3+1/3x=5/3x-5/3 | | 114=14x-12 | | 114+14x-12=180 | | 23+13x=53x-53 | | 13x-8+123=180 | | 123=13x-8 | | 4x+9+6x=180 | | 2/3+1/3x=5/3x-5/3 | | 2x-x-2/3=5x-7/2 | | 9x-32+2x+3=180 | | 5n-3=4 | | 2/3x+8=3/5x+10 | | 10x+16=27x-21 | | 2(6x–11)+3x=143 | | -20-(2x-8)=0 | | 1.7(3-2x)=5.9x-11.64 | | 3-2(x-7)=3 | | 3-2(x7)=3 | | x/11=11/38 | | 4x+20-2x+38=0 | | 0=248(t)-16t^2 | | 5x^2+200x-1500=0 | | 84=(x+2)² | | 8x+2+5x-4=180 | | 8s−12=−8 | | 3/4x=2/1 | | 2^2x-4=68 | | -3(4c+6)-8=-50 |